a Analisis Rasio Profitabilitas terhadap Kinerja Keuangan PT Gowa Makassar Tourism Development Tbk (2020-2022) - Nadia Nurayanti; Fausiah Fausiah; Elisabeth Ambalele (Institut Agama Islam Negeri Palopo, 2024)
This study analyzes the effect of profitability ratios on PT Gowa Makassar Tourism Development Tbk's financial performance in 2020-2022. The method used is quantitative analysis, which calculates the return on assets (ROA), return on Equity (ROE), and net profit margin (NPM) ratios from the company's financial statements. The results show that ROA increased sharply in 2021 but decreased in 2022. ROE also experienced a similar trend, while NPM fell drastically from 59% in 2020 to 1.13% in 2022. This decline reflects the company's operational efficiency and cost control challenges, negatively impacting profitability. These findings emphasize the need for strategic evaluation to improve financial performance in the future.